Kemampuan Guru dalam Menilai Aspek Afektif - Mohzana, Mohzana; Murcahyanto, Hary; Fahrurrozi, Muhammad (JOEAI (Journal of Education and Instruction), 2021)
This study aims to find out the ability of MTs NW teachers in Aikmel Subdistrict to assess affective aspects in Indonesian school year. The type of research used in research is descriptive research. The subjects of the study were Indonesian teachers who were selected by purposive sampling or aiming samples. The object of this study is assessment in the affective realm of students. The results showed that teachers in assessing the affective realm did not make the right indicators according to operational verbs, the assessment also did not pay attention to SK-KD and the characteristics of the affective realm. Therefore, it is necessary to provide an affective domain assessment that is using non-test assessment, in this study it is recommended to use questionnaires to measure all characteristics of affective realms namely attitudes, interests, self-concepts, values and morals. The conclusion that can be taken from the results of this study is that the overall assessment instrument of the affective realm has been good and can be used as an evaluation tool in the affective realm by teachers. Suggestions that can be submitted based on this research, for Indonesian teachers who want to develop affective field assessment instruments should be considered difficulties in the preparation of instruments. Keywords: Teacher's Ability; Affective Aspects Assessment